The effect of AlOOH boehmite nanorods on mechanical property of hybrid composite coatings - Chen, Q. (2012)
AlOOH boehmite nanorods were used as a filler to develop sol gel based and polymer based hybrid composite coatings. The fracture toughness of the composite coatings was significantly improved by the nanorods as supported by nanoindentation test on sol gel based coatings and buckling test on polymer based coatings. The better fracture toughness of the nanorod filled composite than the conventional composite can be explained by the high aspect ratio of rigid nanorods, the orientation of nanorods along surface direction observed in the composite coatings, as well as chemical affinity between nanofillers and the matrix after they reacted with organosilane.